Optimization of zinc oxide thin films for silicon surface acoustic wave resonator applications - Sidek, Fatini; Nordin, Anis Nurashikin; Othman, Raihan (Trans Tech Publications, Switzerland, 2012)
High quality ZnO thin films are required to produce CMOS SAW resonators operating with low losses and high Q. This work intends to develop high performance CMOS SAW resonators through optimization of both the quality of the ZnO and the design of the SAW resonator. Zinc oxide was chosen for this work as the piezoelectric material due to its superior acoustic propagation properties and compatibility with integrated circuit fabrication techniques. ZnO has demonstrated good performance characteristics for a variety of piezoelectric devices. For optimization of the quality of the deposited ZnO thin film, different RF-sputtering conditions will be used to investigate which condition produces the best piezoelectric quality of the ZnO thin film. The experiments were carried using Taguchi optimization method, which studies a large number of variables with a small number of experiments.